KONSEPSI PEMBERDAYAAN ZAKAT PRODUKTIF - Nurdin, Ridwan; Iqbal, Muhammad; Khalidi, Muhadi (ALQALAM, 2018)
This study discusses the empowerment of productive zakat aimed at fostering the welfare of mustahik. This research is a programme on the implementation of the Zakat Amil Agency in the distribution of zakat. This research uses qualitative method in order for it be relevant to the results achieved. The sources of the data in this study are relevant literature both in the form of books, journals and articles used to compile theories about problems that are the objects of the research. Based on our findings, the mustahik receive zakat from the Zakat Amil Agency with the scheme of productive zakat. In relation to the data compilation in this study, the techniques used include the activities and the development of the Zakat Amil Agency in daily activities to manage zakat and mustahik’s productive zakat in organizing the programmes. Data analysis was conducted by structuring data in the form of compiling, classifying and testing data during the research. Data analysis was carried out to describe the processes and results of examinations from transcripts and notes and other materials. In relation to the qualitative approach, the data analysis is conducted in three steps, namely data reduction, data presentation, and reduction of conclusions.